International Comparisons of Government Expenditure - Heller, Peter (Occasional Papers; Occasional Paper, 1982)
Many studies on International tax compaisons have been undertaken since the early 1970s. While controversial, such studies have facilitated more subtle comparisons of a country's tax performance than would be afforded by focusing on its simple tax ratio.